The Wild Woman of Cincinnati : Gender and Politics on the Eve of the Civil War - Pierson, Michael D. (Book collections on Project MUSE., 2023)
"People looking for entertainment in Cincinnati in 1856 had many options. Choices ranged from high culture to shows barely above the level of the tawdry. Among their options that summer was a "Wild Woman" display, which purported to exhibit a young woman captured while living a feral life beyond the US frontier. The show consisted of an uncommunicative woman clothed in rags chained to a bed. It was almost assuredly a hoax. Nevertheless, the exhibitor's tale used a fascination with the frontier and the idea of "whiteness in danger" to appeal to enough people to keep the show open for over two months. It ended at the behest of local activist women who used their influence to prompt a Cincinnati judge to examine the exhibit. The court then used force to subdue, render unconscious, and undress the Wild Woman before several male doctors, who advised her admission to an asylum. The judge then declared her insane. She remained silent throughout the ordeal, leaving doctors to invent a series of rather bizarre and decidedly gendered case histories to explain her mental incapacitation. In his fascinating history of the "Wild Woman," Michael Pierson uses the exhibit and its captive female to explain a great deal about the United States in 1856, especially the importance of gender to understand political allegiances and access to power. The divisive politics of the era led to much disagreement among patrons about the silent woman. Democrats and Republicans saw different women when they looked at her. They could not agree on who she was, what she meant, or what they should do with her. Partisan editors, judges, and doctors projected their own ideas about women and men onto the blank screen of the mute woman and revealed themselves as well as the divided nature of their country. They also repeatedly demonstrated how much power men had over women in the process. As much as this is a story about the looming civil war, it is also about the nascent woman's rights movement and the necessity of women's political and social empowerment. The Wild Woman of Cincinnati took on many meanings during her moment as a star, but all of them come back to the harsh reality that the city and the nation allowed the exhibitor to "own" her as his "pet" and to display her without any evidence that she had granted consent"--